The Impact of Embedded iPad Use on Student Perceptions of Their Digital Capabilities - Matt Elphick (MDPI AG, 2018)
Digital capabilities are recognized as key skills that students must possess to learn and work in our increasingly digital world and have been the subject of a growing focus over recent years. Similarly, smartphones and, to a lesser degree, tablets are now ubiquitous within the student body, and many academics are beginning to leverage these devices for the purposes of learning and teaching in higher education. To further explore the possibilities of mobile technology, the iPilot project was created to explore the effects that embedded iPad use had on undergraduate students’ creativity, ability to collaborate with their peers and their perception of their digital capabilities. Focusing on the digital capabilities aspect of the project, this paper explores the results gathered. While the results are mixed, when combined with data taken from the Joint Information Systems Committee (JISC) Digital Experience Tracker, it does appear that using iPads in the university classroom can have a positive impact on certain digital behaviors and students’ perceptions of their digital skills.